2001
DOI: 10.1023/a:1010644217648
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum as a delivery system for gene therapy of chemically induced rat mammary tumors

Abstract: A fundamental obstacle in cancer gene therapy is the specific targeting of therapy directly to a solid tumor, and no systemic delivery system yet exists. A strain of domestic bacteria, Bifidobacterium longum, which is nonpathogenic and anaerobic, selectively localized to and proliferated in 7,12-dimethylbenz[a]anthracene-induced rat mammary tumors after systemic application. We further ascertained the tumor specificity of genetically engineered, as well as wild-type, Bifidobacterium longum. This is the first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 11 publications
1
110
0
2
Order By: Relevance
“…Results of the present study demonstrate an important advantage of the use of a facultative anaerobe, such as S. typhimurium, over obligate anaerobes, such as Clostridia 16 or Bifidobacteria, 14,15 which are confined to the anaerobic regions of tumors and therefore, cannot target its vascular system. Our results suggest that tumor vascularity influences the efficacy of A1-R bacteria.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Results of the present study demonstrate an important advantage of the use of a facultative anaerobe, such as S. typhimurium, over obligate anaerobes, such as Clostridia 16 or Bifidobacteria, 14,15 which are confined to the anaerobic regions of tumors and therefore, cannot target its vascular system. Our results suggest that tumor vascularity influences the efficacy of A1-R bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Bifidobacterium longum has been shown to selectively grow in hypoxic regions of tumors following intravenous administration. This effect was demonstrated in 7,12-dimethylbenzanthraceneinduced rat mammary tumors by Yazawa et al 14,15 Vogelstein et al created a strain of Clostridium novyi, an obligate anaerobe, which was depleted of its lethal toxin. 16 This strain of C. novyi was termed C. novyi NT.…”
Section: Coleymentioning
confidence: 99%
“…6 These plasmids, however, could not express foreign gene in Bifidobacterium, which hampered broader application of Bifidobacterium as a specific gene delivery system for cancer gene therapy although successful expressions of foreign gene in the Bifidobacterium have been reported. [7][8][9][10][11] Our previous studies demonstrated that pBV220, an E. coli-derived vector, could express foreign gene in B. adolescentis and B. longum. 9,10 However, it was found to be unstable in Bifidobacterium in the absence of selective antibiotics, which was particularly disadvantageous for prolonged and large-scale cultivation of the plasmid-bearing cells.…”
Section: Introductionmentioning
confidence: 99%
“…Though some Bifidobacterium-Escherichia coli shuttle vectors have been constructed in recent years, only some of them expressed foreign genes successfully. [23][24][25][26][27][28][29][30][31][32][33] In our previous studies, we developed a shuttle vector (pBV22210), which could replicate stably and expressed recombinant human endostatin in both E. coli and B. longum. B. longum transfected with pBV22210-endostatin showed a clear inhibitory effect on the growth of mouse solid liver tumor in vivo.…”
Section: Introductionmentioning
confidence: 99%